PERAWATAN LUKA UNTUK PENCEGAHAN INFEKSI PADA TALI PUSAT BAYI DI BPM BIDAN ANOVA SARAGIH, S.KEB - Marsela, Yenny; Dwi Anjani, Arum (Universitas Batam, 2024)
Carrying out umbilical cord care is very important to prevent infection. The aim of umbilical cord care is to prevent tetanus in newborn babies, so that the umbilical cord remains clean, germs do not enter so that infection does not occur in the baby's umbilical cord. Tetanus is caused by clostridium tetani, which is a germ that releases toxins (poison), which enters through the umbilical cord wound, due to unclean care or procedures. Providing midwifery care in the form of education to mothers about how to properly care for the umbilical cord to prevent infection in newborns in accordance with service standards for independent practicing midwives. The method used in this research method was written based on a case study report of midwifery care for newborns using a descriptive observational method with a midwifery care approach. Umbilical cord wound care is intended as an act of caring for and cleaning the umbilical cord, as well as to prevent infection in the baby's umbilical cord and speed up healing of wounds left by cutting the umbilical cord. Improper care for umbilical cord wounds in babies will result in infections that can result in death. This disease is caused by the entry of tetanus germ spores into the body through the umbilical cord, either from unsterile instruments, use of drugs, powders or leaves sprinkled on the umbilical cord which can cause infection.